Morphological diversity and protein concentration of Lupinus spp. in central-eastern region of the state of Puebla, Mexico - Lagunes-Espinoza, Luz del Carmen; López-Upton, Javier; García-López, Eustolia; Jasso-Mata, Jesús; Delgado-Alvarado, Adriana; García de Los Santos, Gabino (Instituto de Ecología, A.C., 2012)
The present study aimed to characterize the diversity of Lupinus genus (Leguminosae) present in agricultural and forest ecosystems of eastern central region of the Mexican state of Puebla, and to estimate seed protein concentration in species identified. Natural populations were located from 2600 to 4000 m above sea level in soils with neutral (7.1) to acid (4.7) pH, with high content of organic matter (> 7.8%) and low levels of exchangeable K+ (< 6 cmol+g-1). Natural populations of Lupinus showed a great morphological variability result of diversity of species in this genus present in the study area. Four species were identified based on their morphological characteristics and altitudinal range: L. campestris, located at altitudes of 2600 to 3052 m, along edges of corn and faba bean crops or natural vegetation areas in the presence of Juniperus deppeana, various species of Pinus and Abies religiosa; L. exaltatus from 2778 to 2865 m in forests of P. montezumae; L. hintonii at 3080 m associated with Abies religiosa; and L. montanus, at altitudes above 3000 m associated with P. hartwegii, P. montezumae, P. rudis and Abies religiosa. High concentration of seed protein was observed within and between species. Among species, the average protein concentration ranged from 328 to 387 g kg-1 of dry matter (DM). Between the species, the concentration ranged from 317 g kg-1 (a population of L. exaltatus) to 481 g kg-1 DM (a population of L. campestris).